ANALISIS MANAJEMEN RESIKO OPERASIONAL MEBEL KAYU SEMBARANG KAMPUNG (STUDI PADA CV. KARYA MEGA MANDIRI) - Ikhwani, Yurida; Syaharman, Syaharman; Falahi, Adrial (JURNAL MUTIARA MANAJEMEN, 2022)
This study aims to determine business risk management on wood in any village. The data analysis technique used in this research is descriptive qualitative. The subjects in this study were CV. Mega independent work and the object of this research is business risk management. Data collection techniques in this study were observation, documentation and interviews. The results of this study were seen from the results of interviews with CV. Mega Mandiri's work to the community so far has implemented business risk management properly. In dealing with the risk of Human Resources CV. Karya Mega Mandiri conducts direct supervision to avoid fraud in the production process. This is intended to reduce risks that may occur, because risks can come from outside or within the company so that risk management is very helpful in dealing with various kinds of risks that exist.